Evaluation of FTIR, Macro and Micronutrients of Compost from Black Soldier Fly Residual: in Context of Its Use as Fertilizer - S. Sukamto; Ali Rahmat (ASEAN Journal of Science and Engineering, 2023)
The extensive use of chemical inorganic fertilizers promotes the degradation of agricultural land quality and leads to various environmental contaminations. Owing to these problems, the alternative way called “organic farming” has been developed through the use of organic fertilizers including compost.  In this study, compost product obtained from composting process by using larvae as the biological agent has been prepared. Macronutrients (i.e. N, P, K, Ca, and Mg) and micronutrients (i.e. Mn, Fe, Cu, Zn, and Ni) have been determined using Inductively Coupled Plasma-Optical Emission Spectrometry, Walkey and Black method, Kjeldahl method, and P Bray-1 method, which showed sufficient content and meet the standard value. Analysis and the comparative study showed that the compost product can be used as a fertilizers substitute. The compost from residual offers more economic, great availability, and environmentally friendly fertilizers for agricultural purposes.